Poorly differentiated gastro-entero-pancreatic neuroendocrine carcinomas: Are they really heterogeneous? Insights from the FFCD-GTE national cohort. (July 2017) - ,; Stephanie, Laetitia; Borbath, Ivan; Castex,; Petorin, Caroline; Terrebonne, Eric; Bouhier-Leporrier, Karine; Suc, Etienne; Hautefeuille, Vincent; Bourgeois, Vincent; Cany, Laurent; Dewaele, François; et al.
Abstract: Background: Diagnosis and management of poorly differentiated gastro-entero-pancreatic (GEP) neuroendocrine carcinomas (NECs) remain challenging. Recent studies suggest prognostic heterogeneity. We designed within the French Group of Endocrine Tumours a prospective cohort to gain insight in the prognostic stratification and treatment of GEP-NEC. Patients and methods: All patients with a diagnosis of GEP-NEC between 1st January 2010 and 31st December 2013 could be included in this national cohort. Adenoneuroendocrine tumours were excluded. Results: 253 patients from 49 centres were included. Median age was 66 years. Main primary locations were pancreas (21%), colorectal (27%), oesophagus-stomach (18%); primary location was unknown in 20%. Tumours were metastatic at diagnosis in 78% of cases. Performance status (PS) at diagnosis was 0–1 in 79% of patients. Among the 147 (58%) cases reviewed by an expert pathological network, 39% were classified as small cell NEC and 61% as large cell NEC. Median Ki67 index was 75% (range, 20–100). Median overall survival was 15.6 (13.6–17.0) months. Significant adverse prognostic factors in univariate analysis were PS > 1 (hazard ratio [HR] = 2.5), metastatic disease (HR = 1.6), NSE > 2 upper limit of normal [ULN]; HR = 3.2), CgA > 2 ULN (HR = 1.7) and lactate dehydrogenase >2 ULN (HR = 2.1). After first-line palliative chemotherapy (CT1) with platinum-etoposide (n = 152), objective response, progression-free survival and overall survival were 50%, 6.2 and 11.6 months; they were 24%, 2.9 and 5.9, respectively, after post-CT1 FOLFIRI regimen (n = 72). Conclusions: We report a large prospective series of GEP-NEC which show the predominance of large cell type and advanced stage at diagnosis. Prognosis was found more homogeneous than previously reported, mainly impacted by PS and tumour burden. Highlights: Large cell type GEP-NEC and advanced stage at diagnosis are predominant. Prognosis is mainly impacted by performance status, NSE and tumour burden. First-line platinum-etoposide allows 50% of response and 6.2 months of PFS. Second-line treatment has low efficacy and must be improved.